(untitled) (diségno, 2026)
This paper analyses the American work of Vittorio Giorgini (1926-2010), a Florentine architect who, starting in 1969, found in New York the ideal context for developing visionary and experimental research. The study focuses on the projects Walking Tall (1982-1983) and Hydropolis (1981-1982), emblematic examples of an architectural language that combines geometric rigor, structural experimentation, and strong expressive intensity. In these works, geometry acts as the generative principle governing form, structure and function, anticipating approaches that can today be associated with parametric thinking. Through the analysis of archival drawings and manuscripts, the research identified the elementary geometric units and the aggregation logics underlying the projects, translating them into dynamic digital models through VPL (Visual Programming Language) procedural modelling tools. This method made it possible to validate the consistency of Giorgini’s design grammar, confirming its relevance and translatability into flexible generative systems. The digital reconstruction does not operate as a mere reproduction, but as a testing environment capable of verifying the feasibility of the proposals, transforming utopian vision into operative hypothesis. The paper thus highlights the anticipatory value of Giorgini’s research, a still under-recognized figure who combined geometric experimentation, attention to the urban context, and the aspiration towards alternative models of the city, and who can today be considered among the forerunners of parametric architecture.